Singapore, A Growing Economic Titan from South East Asia - Ignatius Hubert Tantra (Jurnal Sentris, 2018)
Singapore has one of the fastest economic development pace throughout South East Asia. Despite the fact that by land mass, it is not the biggest or the most fertile country. By demographic factor, it is not the most populated nor the most culturally diverse country. It also didn’t have the natural resources that its neighboring countries boasted as their main commodity. Yet, Singapore is a country with one of the most efficient implementation of living space, land usage, and education programme in the world. Because of its greatness, Singapore can be put in the same class with the others developed countries in the world. This is despite all the handicap that this country has, through the thick and thin of its history. The author believes that these successes can be atributted mostly to the efficient leadership of Singapore as a nation state in the international system, and that these successes can be adapted throughout Asia, and the world as a whole. This essay was made exactly to achieve this successful impact on ASEAN’s countries economics. In this writing, the author will examine what makes Singapore such a great economic titan, and how it can turn its unlikely position into a flourishing market economy and becoming a model for other developing countries to replicate, with institutional leadership. All of these, for the purpose of learning, and in the bid of rejuvenating economic vigor that most Asian countries and developing countries needed to keep up and even compete with more prominent countries in the international political system of the world.